Ecology of E-Learning - Babak, Ekaterina (Educational Challenges, 2023)
Purpose. The paper deals with the role of new digital technologies in learning. The tasks for the research are the following: to bring readers with an up-to-date range of new learning and teaching technologies, explore the notion of "ecology of e-learning" by analyzing the dynamics of student and teacher interactions in e-learning environments, investigate critically the ways in which technologies can create openings for new pedagogical practices, and also at times fossilize old pedagogical practices that perhaps should have been already abandoned, explore the "affordances" framework as a checklist used to analyze educational technologies and their associated pedagogical practices. Methodology. The methods of the educational research context, data collection, data analysis and reporting of the students’ responses have been applied. Some interviews have been conducted in this study to receive the answers of different students and lecturers at Kharkiv University of Humanities ‘People’s Ukrainian Academy’. The basis for our research has been scientific and pedagogical studies relevant to future foreign languages teachers’ professional training in distance education conditions. Results. Didactic and reflexive pedagogy have been analyzed and compared. The following aspects have been analyzed: ubiquitous learning, active knowledge making, multimodal meaning, recursive feedback, collaborative intelligence, metacognition, differentiated learning. It is emphasized that digital ecologies and the new learning spaces afforded by technologies provide us with the availability to have a group of learners in a space where not all of them have to be tracking the same page, the same task at the same time. It is possible to create learning experiences for individuals and for groups with specific needs and to be able then to pace either the whole group or to pace the individual, to track an individual or to track the whole class depends on the learning process, either for the whole class or the individual, in order to adjust the instruction, the data, the information that the learner or the class has, so that they are able to meet their goals. It is highlighted that every child in the classroom even if they are the same age, or if they are the same background are unique in some way. The orientation to learning or their behavior, or their understanding of their purpose is molded by each one’s life experience. Educators have a responsibility to show that every learner is transformed, progresses, is able to understand and engage with and represent knowledge in a way that meets their needs of being an educated person that can move through the formal school system. Conclusions. Working within digital spaces allows us to harness the attention of every learner, to tailor educational process for their needs, to track whether they are performing or not and to adjust what we are doing. It provides us with the ability to make sure that all learners can be engaged. It means a different kind of plan. It certainly means collaborating. Collaborative intelligence for teachers in preparing, work and instruction in this space is also a key to the kinds of solutions that possible. It means designing lessons with the learners in mind, not only with just pacing ones way through the standards or with any kind of curriculum, it is aligning the standards to individual’s needs and deconstructing them and reconstructing them in order to pace individuals and groups so that they can progress towards higher or to goals. It means for the teacher expanding their instructional repertoires to be able to address all the learners in the classroom and as well as expanding the capacity to work with others to bring in experts through the digital ecologies that might be able to support individual learners.